Evaluation of substrate consumption kinetics in different support materials for biotrickling filters aiming biogas desulfurization - Hidalgo, Letícia Ferraresi [UNESP]; Santos, Jessyka Lima; Tayar, Samir Prioto [UNESP]; Sarti, Arnaldo [UNESP]; Palmieri, Maurício Cesar [UNESP]; Guerrero, Renata De Bello Solcia; Bevilaqua, Denise [UNESP] (Trans Tech Publications, 2017)
Biogas is a renewable energy source that can be used to produce heat and energy, replacing fossil fuels. The main limiting factor using biogas is the presence of contaminants like H2S, which is the most important causing corrosion and other environmental problems. Biotrickling filters is considered a promising technology to remove such contaminant from the biogas, but the selection of inexpensive and durable supports is an important step for this operation. In the present study, several different support materials were used for the microorganisms immobilization such as Polyvinyl Chloride (PVC), Polyethylene Terephtalate (PET) and Polytetrafluoroethylene (Teflon®) in comparison with the open pore polyurethane foam (OPP). To evaluate the consumption of thiosulfate by chemolitotrofic microorganisms, each column was packed with the desired support material as the biotrickling filters. The kinetics of the substrate consumption in different cycles for each support was distinct suggesting different microbial colonization. The materials tested have presented results very similar to polyurethane foam, which has already known by its efficiency on biogas desulfurization, unless Teflon, that showed a divergent result with the increase of the substrate concentration in the system.
Keywords: Biodesulfurization; Biogas; Biotrickling filter; Support Material